COMPARATIVE ANALYSIS OF THE E-GOVERNMENT DEVELOPMENT INDEX: A CASE STUDY OF SINGAPORE AND AFGHANISTAN - Ramadhan, Sukma Aditya; Purnomo, Eko Priyo (Sosiohumaniora, 2024)
This study analyzes the differences in the development of e-government in Singapore and Afghanistan using the E-Government Development Index (EGDI) indicators which include the Online Services Index (OSI), Human Capital Index (HCI), and Telecommunication Infrastructure Index (TII). The findings show that Singapore's success in e-government is underpinned by strategic investments in ICT infrastructure, the adoption of innovative policies such as the "Smart Nation," and sustainable human resource development. In contrast, key challenges in Afghanistan include political instability, corruption, limited basic infrastructure, and low levels of digital literacy, all of which hinder the implementation of e-government. In addition, the study reveals the importance of a cross-sectoral approach and community engagement to create an inclusive digital ecosystem, an aspect that is not measured in the EGDI framework. This research offers new insights into digitalization strategies that developing countries can implement to accelerate their digital transformation.